Implementasi Kurikulum Merdeka di SDN 2 Pasuruan dalam Meningkatkan Akhlak Beragama - Hidayat, Nurdin; Yuberti, Yuberti; Akmansyah, Muhammad; Tuala, Riyuzen Praja (Pedagogia: Jurnal Ilmiah Pendidikan Dasar Indonesia, 2024)
The curriculum is present as a guide used by educators where the curriculum undergoes various changes as a form of adaptation to a dynamic era. One of them is by implementing an merdeka curriculum where this curriculum tends to be considered as a new one. This curriculum is still in the process of being implemented gradually. Nevertheless, there are some schools have implemented merdeka curriculum. Those schools have emphasized independent learning according to the needs and characteristics of students. This study aims to determine and analyze the implementation of the merdeka curriculum at Public Elementary School 2 Pasuruan in improving religious morals. This research is a descriptive research with a qualitative approach. While the data analysis used is the Miles and Huberman model which includes data reduction, data presentation and conclusion drawing or verification. The results of this study indicate that the implementation of the merdeka curriculum at Public Elementary School 2 Pasuruan has started to run effectively in improving religious morals. The implementation of the independent curriculum is a very good breakthrough to be implemented, because in its policies it can make it easier for teachers to teach basic and important material to students without having to be burdened with other essential material.